A influência de implantes dentários em imagens de radiografia periapical, panorâmica e tomografia computadorizada de feixe cônico - Felix, Rafael Perdomo (2015)
Imaging exams performed in areas with the presence of metallic materials such as dental implants can decrease the accuracy of the exams due to metallic artifacts production generated in the peri-implant region. A sample of 21 dental implants placed in 10 patients with Branemark protocol prostheses was evaluated in the periimplant area in image exams of the post-surgery control using periapical radiography (paralleling technique), panoramic radiography and cone-beam computed tomography (CBCT). The radiographic density of different areas bounded near the dental implants were calculated and compared considering their locations and the imaging exams using the software ImageJ. Regarding the different imaging exams, the CBCT showed significant differences between the measured areas (p<0.001), while in periapical (p=0.430) and panoramic (p=0.149) radiographs did not occur significant difference between the gray mean values in these areas. Comparing the areas in the three exams it was observed larger values next to the implants in all exams: CBCT (126.20 and 127.44) panoramic radiography (106.51 and 106.09) and periapical radiography (120.32). The more distant areas and the areas closest to neighboring implants had significant different values in the two reconstructed images of CBCT when compared to the panoramic and periapical radiographs. The interference of dental implants in acquiring radiographic and tomographic exams was confirmed by altered radiographic density mean values in the peri-implant area. Comparing the three exams it was noticed that the CBCT image showed the most significant interference of the dental implants.